Optimization of LPTQ Extracurricular Governance: Increasing Student Potential Through Strengthening Teacher Competencies - Abdul Aji Ibrahim; Mahariah Mahariah (Institut Agama Islam An-Nawawi Purworejo, 2024)
This research aims to analyze the competence of Al-Qur'an Hadith teachers in increasing students' potential. The research method used is qualitative based on case studies with data collection techniques through observation, interviews and documentation studies. The research results show that LPTQ extracurricular management includes planning in (a) implementation time, (b) types of activities, and (c) coaching methods. The implementation of LPTQ activities is organized by the Al-Qur'an Hadith teacher as the supervisor. Teacher competence in increasing student potential consists of pedagogical and personality competence. Teacher pedagogical competence includes understanding the knowledge of the Koran and methods of developing students. This competency is reflected in the teacher's understanding of the art of reading the Al-Qur'an and the use of methods such as singing poetry, memorizing, and tasmi which are adapted to the type of coaching. Apart from that, the teacher's wise, wise and mature personality is the basis for teachers to set a good example to students. Implementation of LPTQ activities includes various coaching such as syarhil Qur'an, fahmil Qur'an, tahfidz Qur'an, khattil Qur'an, and recitations of the Qur'an.